Hubungan Identitas Moral dengan Perilaku Cyberbullying pada Remaja - Fitriah Fitriah; Meta Aldila Listiya; Nisma Nisma (Malahayati Nursing Journal, 2025)
ABSTRACT The increasing internet penetration among adolescents has brought both benefits and challenges. While it facilitates access to information, it also raises social issues such as cyberbullying, which negatively impacts adolescents' mental and physical health. This study aims to analyze the relationship between moral identity and cyberbullying behavior among adolescents at SMPN 21 Pontianak, West Kalimantan. An analytical survey with a cross-sectional design was conducted, involving 90 adolescents selected through accidental sampling. Data were collected using the Moral Identity Questionnaire (MIQ) and the Cyber Victim and Bullying Scale (CVBS). The study revealed a significant negative correlation between moral identity and cyberbullying behavior (r = -0.326; p = 0.002). Adolescents with stronger moral identity are less likely to engage in cyberbullying, while moral disengagement increases the risk of such behavior. Social support from family and peers also strengthens adolescents' moral identity. Moral identity serves as a protective factor against cyberbullying among adolescents. A holistic approach, including moral education in schools, parental involvement, and community support, is essential to prevent cyberbullying. Future studies should explore other environmental factors influencing this behavior. Keywords: Moral Identity, Cyberbullying, Adolescents, Moral Disengagement, Moral Education  ABSTRAK Peningkatan penetrasi internet di kalangan remaja membawa manfaat sekaligus tantangan. Di satu sisi, akses terhadap informasi menjadi lebih mudah, tetapi di sisi lain, cyberbullying menjadi masalah sosial yang berdampak negatif pada kesehatan fisik dan mental remaja. Penelitian ini bertujuan untuk menganalisis hubungan antara identitas moral dan perilaku cyberbullying pada remaja di SMPN 21 Pontianak, Kalimantan Barat. Penelitian ini menggunakan desain survei analitik dengan pendekatan cross-sectional. Sebanyak 90 remaja dipilih sebagai sampel menggunakan teknik accidental sampling. Data dikumpulkan melalui Moral Identity Questionnaire (MIQ) dan Cyber Victim and Bullying Scale (CVBS). Hasil penelitian menunjukkan adanya hubungan negatif yang signifikan antara identitas moral dan perilaku cyberbullying (r = -0,326; p = 0,002). Remaja dengan identitas moral yang lebih kuat cenderung tidak terlibat dalam cyberbullying, sedangkan pelepasan moral meningkatkan risiko perilaku tersebut. Dukungan sosial dari keluarga dan teman sebaya juga memperkuat identitas moral remaja. Identitas moral berperan sebagai faktor pelindung terhadap perilaku cyberbullying. Pendekatan holistik, termasuk pendidikan moral di sekolah, keterlibatan orang tua, dan dukungan komunitas, diperlukan untuk mencegah cyberbullying. Penelitian lebih lanjut direkomendasikan untuk mengeksplorasi faktor lingkungan lainnya. Kata Kunci: Identitas Moral, Cyberbullying, Remaja, Pelepasan Moral, Pendidikan Moral